Transformation of the CIRC (Cooperative Integrated Reading and Composition) Model to Enhance Qira'ah - Diana, Rita; Setiyawan, Agung; Bagas Purnama, Boby; Nanda Safitri, Siska; Ziad Al-Fain, Mumammad; Wazkia, Hanif; Riskiyah, Riskiyah (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to describe the implementation of the Cooperative Integrated Reading and Composition (CIRC) model in learning reading skills in the classroom. The CIRC model was chosen because it effectively improves students' literacy skills through collaboration in small groups, compared to other collaborative approaches. This study's background is students' low reading ability in Arabic language classes, so innovation is needed in learning methods. This study uses a qualitative approach with a case study design. The subjects of the study consisted of thirty students in one class. Data collection techniques include observation, in-depth interviews, and document analysis. Observations monitor the implementation of the CIRC model, focusing on teacher-student interactions and group dynamics. Interviews with teachers and students explore their experiences and perceptions of the CIRC model. Document analysis assesses student work, including summaries and shared notes. The results of the study indicate that the CIRC model increases students' active participation and cooperation, as reflected in their enthusiasm and motivation during learning. In addition, students' reading comprehension increases, as reflected in interviews and observations that show students find it easier to understand the text. However, there are obstacles, such as time constraints, differences in reading abilities between students, and teachers' limited experience in implementing this model.